Pengaruh Budaya Keselamatan Pasien terhadap Sikap Melaporkan Insiden pada Perawat di Instalasi Rawat Inap Rumah Sakit Tk. II dr. Soepraoen - Anggraeni, Dewi; Ahsan, .; Azzuhri, Misbahuddin (Universitas Brawijaya, Indonesia, 2016)
Abstract: Patient safety culture in the organization, directly related to the individualattitudes and motivation to report any patient safety incidents. Openness attitudes to report any incidents is one indicator of patient safety culture in the internalization of individual behavior. Attitudes that do not support incident reporting on the staff, especially the nurses, will hamper efforts to create safe care because the absence of an incident report will have an impact that is hospital not aware of any potential warning of the dangers that can cause errors. This study is non experimental research with the aim of using correlative descriptive cross sectional design. The independent variable in this study is a patient safety culture while the dependent variable is the attitude of patient safety incidents reported. The results showed that simultaneous patient safety culture significantly influence the attitude of reported incidents. Partially organizational learning and continuous improvement does not significantly influence the attitude of patient safety incidents reported, Teamwork significant influence on the attitude of reported incidents, openness of communication significantly influence the attitude of reported incidents and the responses not to punish a mistake does not significantly influence the attitude of reported incidents. Teamworkhas dominant influence on the attitude of patient safety incidents reported